EVALUASI INPUT KELAS IBU HAMIL DI WILAYAH KERJA PUSKESMAS SUKOLILO - Siti Rochimatul Lailiyah (NHM PRESS, 2019)
Interpersonal education in pregnancy program is a means to learn together about maternal health in the form of face to face in a group that aims to improve the knowledge and skills of mothers in pregnancy,childbirth, postpartum and newborn care. 8 of 10 mothers have not been able breastfeeding correctly when they have Interpersonal education in pregnancy program. Aim of this study is to identify a picture of the participants, facilitators, facilities and infrastructureclass of pregnant women in the region work of Puskesmas Sukolilo. This research uses descriptive quantitative research with a case study approach. The variables used were input component class pregnant women, participants, facilitators, facilities and infrastructure. The study population is all classes of existing maternal health center working area Sukoliloas many as 13 classes for pregnant women. The data are collected by using questionnaires,observation, and interviews. The results showed that the majority of class participants mom Pregnant aged 21-25 years is 78 respondents (77%). In which The majority of participantsprimary and junior education level that is 84 respondents (83%) and mostly participants as housewife is 67 respondents (66%). Meanwhile the knowledge of participants almost half less that 49 respondents (48%), and class facilitators pregnant women as many as two respondents, both aged > 35 years, educated DIII of midwifery, and trained in facilitating classroom pregnant women. In addition, pregnant mothers-class facilities are available but incomplete and also there are less infrastructure. It is expected that the participants in a class of pregnant women can be group ed according to the level of education and age of pregnancy in order to get the right things, then the facilitator in pregnant mother class should be carried out by midwives in the local area, as well as the means and infrastructure needs to be more completed in order to support class implementation pregnant women to be more optimal and effective.